Potential Benefits of Local Fruits and Vegetables From Jember District As a Biological Learning Source to Get the Highest Income - Sawitri Komarayanti; Elfien Herrianto; Wiwik Suharso (Budapest International Research and Critics University, 2019)
Local fruits and vegetables in Jember District are part of Indonesia's biodiversity, which needs attention. The over supply of imported fruits to the regions can shift the presence of local fruits. Fruits and vegetables are food ingredients that are very beneficial for the body. This research is an exploratory study that aims to analyze the potential of local fruits and vegetables in Jember District as a source of learning high school biology based on local excellence. Analysis of potential learning resources is assessed through curriculum analysis by taking into account the suitability of learning resources with the 2013 curriculum that applies in high school. The results of the study showed that, the facts, concepts, principles and procedures relating to Jember local fruits and vegetables were in accordance with the standards of the contents of high school biology subjects in the 2013 curriculum. Furthermore, the results of the curriculum analysis can be used as a reference for the development of teaching materials based on the potential of local fruits and vegetables in Jember District through adjustments to the 2013 curriculum, the characteristics and needs of students and the ability of high school biology teachers.